EFFECT OF NANOSILVER AND SUCROSE ON POST HARVEST QUALITY OF CUT ASIATIC LILIUM CV. TRESOR - S. VINODH; M. KANNAN; M. JAWAHARLAL (The Bioscan, 2013)
An experiment was conducted under Completely Randomized Design at the Department of Nano science and Technology, Tamil Nadu Agricultural University, Coimbatore during the year 2011-12 to study the effect of different holding solutions with sucrose and silver nano particles on post harvest quality of cut Asiatic lilium cv. Tresor. Uniform sized lilium flower spikes at first bud colour break stage were harvested and kept in holding solutions comprised of Sucrose 2%, Nano Silver (NS) 25, 50 and 75 ppm alone and combinations viz., Sucrose 2%+ NS 25ppm, Sucrose 2%+ NS 50ppm, Sucrose 2%+ NS 75ppm and control (Using de-ionized water). Holding of lilium spikes with Sucrose 2%+ NS 50 ppm resulted in greater water uptake (16.97 g/stem) and flower size (17.82 cm) with maximum vase life of (17.8 days) as compared with (8.3 days) in control.